2020
DOI: 10.1123/jpah.2019-0232
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward Active Lifestyles: The Change of Transit-Related Walking to Work From 2009 to 2017

Abstract: Background: This study explored the percentage change of walking to/from public transit to work from 2009 to 2017 in general and for specific sociodemographic characteristics. Furthermore, this study also examined the sociodemographic characteristics of those who walked to/from transit to work and those who walked 30 minutes or more per day to/from transit to work and compared the difference between 2009 and 2017. Methods: 2009 and 2017 National Household Travel Survey were used. This study used weighted logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…A third (36) found the presence of dependents within households of men of lower socioeconomic status was associated with higher TRPA. Four studies found no association between dependents and TRPA (35,43,52,60). The presence of pets in the household was assessed in three studies (65)(66)(67), with only two nding signi cant association.…”
Section: Living Arrangementsmentioning
confidence: 97%
See 4 more Smart Citations
“…A third (36) found the presence of dependents within households of men of lower socioeconomic status was associated with higher TRPA. Four studies found no association between dependents and TRPA (35,43,52,60). The presence of pets in the household was assessed in three studies (65)(66)(67), with only two nding signi cant association.…”
Section: Living Arrangementsmentioning
confidence: 97%
“…Those who were non-white were more likely to undertake higher levels of TRPA (13,36) than those who were white. Similarly, immigrant and minority populations were more likely to undertake TRPA (60,65) than the remaining native residents. In a study from the US, white participants were more likely to undertake an active commute via bicycle compared to their Hispanic and African-American counterparts (54).…”
Section: Individual Exposuresmentioning
confidence: 97%
See 3 more Smart Citations